Pengaruh Penyuluhan Kejang Demam terhadap Pengetahuan Ibu di Ruang PICU RSUD Aloei Saboe - Mohamad, Rini Wahyuni; Jafar, Cindy Puspita Sari Haji; Indrayati, Anggun (Yayasan Mandar Indonesia, 2025)
Febrile seizures are the most common neurological disorder in children and require urgent treatment. A mother’s knowledge greatly affects how she manages this condition. This study aims to assess the impact of health education on mothers’ knowledge about febrile seizures in children with fever at the PICU of RSUD Prof. Dr. H. Aloei Saboe. Using a pre-experimental one-group pretest-posttest design, 39 mothers were given a single-session health education. Data were collected via questionnaires and analyzed with the Wilcoxon test. Results showed that 74.4% of respondents had good knowledge after the intervention. The study concludes that health education significantly improves mothers’ knowledge, and it is recommended as a routine educational program for mothers.